2021
DOI: 10.1111/ijcp.14544
|View full text |Cite
|
Sign up to set email alerts
|

Can prognostic nutritional index and systemic immune‐inflammatory index predict disease severity in COVID‐19?

Abstract: Background Prognostic nutritional index (PNI) and systemic immune‐inflammatory index (SII) are inflammation‐based novel markers that predict the prognosis in various patient populations. We have investigated the relationship between the disease severity in COVID‐19, and the PNI and SII scores in the present study. Materials and Methods This cross‐sectional retrospective study included 118 hospitalised patients with a confirmed diagnosis of COVID‐19. The patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…There were many predict score models for disease severity in COVID-19 patients, including early warning score, National Early Warning Score 2, q-COVID score, prognostic nutritional index score, Brescia‑COVID Respiratory Severity Scale score, systemic immune-inflammatory index score, COVID-GRAM score, etc. [ 18 , 32 34 ] However, the important information of immune cells was not involved. To predict the risk of progression, we developed the new, predictive PAINT score which contained the NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were many predict score models for disease severity in COVID-19 patients, including early warning score, National Early Warning Score 2, q-COVID score, prognostic nutritional index score, Brescia‑COVID Respiratory Severity Scale score, systemic immune-inflammatory index score, COVID-GRAM score, etc. [ 18 , 32 34 ] However, the important information of immune cells was not involved. To predict the risk of progression, we developed the new, predictive PAINT score which contained the NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, score prediction models, such as prognostic nutritional index (PNI), Systemic immune-inflammatory index (SII) have been used to predict prognosis in COVID-19 patients and other diseases [ 14 18 ]. However, the risk factors related to the progression of COVID-19 symptoms from mild/moderate to severe are still limited and need to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been linked to the severity of inflammatory diseases and infections in several studies 22,23 . It was recently used to predict the prognosis of COVID‐19 infection 24 . In the field of obstetrics, SII has only been used in a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 It was recently used to predict the prognosis of COVID-19 infection. 24 In the field of obstetrics, SII has only been used in a few studies. Tanacan et al showed a relationship between high SII values and negative neonatal outcomes in pregnant women with preterm premature ruptures of membranes (PPROM).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of the bias of study participation in two studies was considered unclear because of the inclusion of patients with severe COVID-19 [28] or those admitted to ICU [32]. The other studies demonstrated a low risk of bias in all domains [11,[19][20][21][29][30][31][33][34][35][36]. The overall risk of bias was considered to be low in the majority (84.6%) of studies.…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%